The impact of the use of BYOD on employees: the case of a South African Bank - Songca, Sanda (My University, 2020)
Traditionally, organisations provided the technology resources to their employees; the ‘Bring Your Own Device’ (BYOD) phenomenon has brought about a technology shift in organisations. BYOD refers to the organisation allowing employees to use their personally owned technology devices for work-related activities. BYOD has been trending as early as 2004 and research has been conducted to understand its implications and studies focused on exploring and understanding the implications of BYOD from an organisation’s point of view. However, limited studies have focused on understanding the impact of BYOD from an employee’s perspective creating a gap in knowledge. This qualitative research study addressed the identified gap by exploring the impact of BYOD on employees within a financial institution in South Africa, Gauteng province. An interpretive approach was followed for this case study, and Activity Theory was used as a lens to address the following research questions:1.What do employees of the financial institution use BYOD for?2.What are the positive and negative impacts of BYOD for employees of the financial institution? The employees that participated in this case study were selected using the purposive sampling method and data was collected through eight interviews. The interviews revealed that employees use several different BYOD devices for work-related activities for various purposes of BYOD use. Cell phones have been found to be the main BYOD device. BYOD was used frequency and primarily for communication purposes. Positive and negative impacts of BYOD were explored from different perspectives. The findings of this study provide an understanding of the positive and negative impact of BYOD use by employees on the facilitation of their work within the organisation. The positive impacts to work facilitation were identified to be increased ‘flexibility and mobility’, better ‘user experience, better ‘employee interaction’ and increased ‘productivity’. The lack of ‘organisational support’ and the ‘incompatibility of devices’ appeared to be the negative impacts to work facilitation. The study also revealed positive and negative personal impacts of BYOD use on the employees, in this regard positive impacts included; increased ‘flexibility and mobility’, increased ‘convenience and efficiency’, greater ‘autonomy’, increased ‘job satisfaction’. While negative impacts of BYOD use on employees were found to be; ‘cost implication’ concerns, ‘work-life overlap’, as well as increased ‘anxiety’ and ‘privacy and security’ concerns. The study suggests that the organisation encourages the use of BYOD and that the employees are more inclined to use BYOD as opposed to the organisation issued device. The study has contributed by exploring the gap in knowledge regarding the impact of BYOD on employees within the South African financial institution. Also, the use of Activity Theory allows for the contribution to the body of knowledge as this theory has not been used as a lens in this context of the study
A research report submitted in partial fulfilment of the requirements for a degree of Masters in Commerce (in the field of Information Systems) at the University of Witwatersrand, Johannesburg, Faculty of Commerce, Law and Management, 2020